2022
DOI: 10.7150/ijbs.68170
|View full text |Cite
|
Sign up to set email alerts
|

The Effects and Mechanisms of Flavonoids on Cancer Prevention and Therapy: Focus on Gut Microbiota

Abstract: Flavonoids are a group of polyphenolic compounds which are ubiquitously found in plants and are consumed as part of the human diet in substantial amounts. The verification of flavonoids' cancer chemopreventive benefits has led to a significant interest in this field. Gut microbiota includes a diverse community of microorganisms and has a close relationship with cancer development. Increasing evidence has indicated that flavonoids exert anticarcinogenic effects by reshaping gut microbiota. Gut microbiota can co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 203 publications
(242 reference statements)
0
14
0
Order By: Relevance
“…The main active ingredient of okra fruit extract is flavonoid. It is broadly acknowledged that flavonoid compounds can modulate intestinal bacteria [ 44 , 45 , 47 , 90 ]. Specifically, baicalin, a plant-derived flavonoid, has a variety of biological activities, which inhibits lung injury by manipulating the production of intestinal bacteria and short-chain fatty acids [ 91 ], improves metabolic abnormalities and intestinal bacteria, and reduces diet-induced metabolic syndrome [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main active ingredient of okra fruit extract is flavonoid. It is broadly acknowledged that flavonoid compounds can modulate intestinal bacteria [ 44 , 45 , 47 , 90 ]. Specifically, baicalin, a plant-derived flavonoid, has a variety of biological activities, which inhibits lung injury by manipulating the production of intestinal bacteria and short-chain fatty acids [ 91 ], improves metabolic abnormalities and intestinal bacteria, and reduces diet-induced metabolic syndrome [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported the isolation of natural free flavonoid compounds and their derivatives from okra fruit [41][42][43]. It is noteworthy that flavonoid compounds are capable of regulating intestinal bacteria and playing a defensive role against diseases [44][45][46][47]. However, there are few clinical and experimental studies at home and abroad to assess the effects of okra fruit extract on SD-induced intestinal flora imbalance and BGPs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that miRNAs can regulate the expression of many genes involved in functional interaction pathways by targeting their mRNAs [ 89 ]. In mammals, miRNAs control the activity of about 50% of protein-coding genes and are indispensable regulators in a variety of physiological and pathological processes by modulating cell proliferation, differentiation, apoptosis, and migration [ 90 , 91 , 92 ]. Therefore, the dysregulation of miRNAs contributes to the occurrence and development of a variety of diseases, including cancer, cardiovascular disease, aneurysm, Kawasaki disease, AD, venous thrombosis, and microvascular complications of diabetes [ 91 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ].…”
Section: Implications Of Ncrnas In Ad Progressionmentioning
confidence: 99%
“…Cancer is the second leading cause of death after cardiovascular disease globally, representing a serious threat to patients’ life and health ( 1 , 2 ). Based on recent statistics from the International Agency for Research, approximately 19.3 million new cancer cases and more than 10.0 million deaths occurred in 2020 ( 3 ).…”
Section: Introductionmentioning
confidence: 99%